Seleção de indicadores ecológicos para a avaliação de planos de restauração de áreas degradadas - Fonseca, Vitor Hugo de Campos (2012)
Ecological indicators are useful tools for forest monitoring. It is known that most restoration projects are doomed to failure due to factors of multiple spheres, and lead to a succession challenge course desirable. The practical relevance of the concept of ecological integrity objectives directed this study that, in general seeks to define practical indicators that can express the conditions of the areas restored in the early stages of restoration (up to 5 years). The indicators were rated from 0 to 3, according to criteria such as ease of measurement, degree of variation of response, ability to predict changes in the system, and weights of 1 to 3, given the degree of importance of each attribute of the indicators . The product of the note by the weight of each indicator expressed a measure of its efficiency (EF). In relation to indicators of composition, structure and function in each area, the AE2 was the one that appeared in better health. In relation to indicators of composition, structure and function of the area Itu (AE2) which was presented in a better position when compared to AE1. Among the indicators of composition, richness, diversity (H ') and the presence of exotic species were the most effective attributes, in relation to the structure, attributes were more effective tree density, the average annual increment of the variables and the dendrometric the indicator function, land cover, competition and sanity were more efficient in detecting changes and changes in areas so fast, convenient and understandable.